A Gas Sensor Based on Fully Tuneable and Electrically Coupled Bulk Acoustic Wave Resonators - Bernardo Madeira; Linlin Wang; Chen Wang; Michael Kraft (Proceedings)
This paper reports on a gas sensor based on two bulk acoustic wave (BAW) resonators electrically coupled with a tuneable capacitor. The weak coupling strength was tuned to its optimal value (achieving maximum sensitivity) by varying the capacitance (without complex filtering, a control circuit as required in the state of the art). A gas sensor was developed based on the electrically coupled BAW resonators by functionalizing one of the resonators with zeolitic imidazolate framework-8 (ZIF-8). It featured a quality (Q) factor of ~2.2 k in air and a resonance frequency of ~6.32 MHz. Such a simple coupling mechanism can be tuned and further extended to coupled resonators in other domains.